Above the clouds : a guide to trends changing the way we work : a project inspired by EFQM with commentary from the worlds of business, the not-for-profit sector and academia.: a guide to trends changing the way we work : a project inspired by EFQM with commentary from the worlds of business, the not-for-profit sector and academia. (2017) - Unknown
No abstract available